Job Demands and Resources, Burnout, and Psychological Distress of Employees in the Chinese Non-profit Sector - Deng, Guosheng; Huang, Chienchung; Cheung, Shannon P.; Zhang, Congcong (Frontiers in Psychiatry, 2021)
The nonprofit sector in China has expanded significantly in the past few decades. However, employees in nonprofits experience high burnout rates, indicating a need to study nonprofit work conditions and their effect on employees. This study applies the job demands and resources (JD-R) model and examines the effects of job demands (JD) and job resources (JR) on burnout and psychological distress experienced by nonprofit employees, recruited via quota sampling, across China (n=233). The findings from path analysis showed that JR had strong and negative effects on burnout and on psychological distress, while JD had strong and positive effects on burnout and on psychological distress. Burnout partially mediated the relations between JD-R and psychological distress. These results highlight the importance of JD-R in reducing burnout and psychological distress in nonprofit employees in China. Research and practice implications are discussed.